Risk estimate and management of insurance companies: the role of underwriter and surveyor in loss control - S. G. Zhuravin; I. S. Kuznetsova; M. M. Surovtsov (Путеводитель предпринимателя)
The system of high-quality risk-management is a provider of financial resistance and stability for insurance company. The point raised in this publication is the lack of formed methodology for creating organized system of effective risk control, and the second one is insufficient professional level of education of underwriter and surveyor - core experts in this system.